Solar Photovoltaic Energy Optimization and Challenges - Soomar, Arsalan Muhammad; Hakeem, Abdul; Messaoudi, Mustapha; Musznicki, Piotr; Iqbal, Amjad; Czapp, Stanislaw (Frontiers in Energy Research, 2022)
The study paper focuses on solar energy optimization approaches, as well as the obstacles and concerns that come with them. This study discusses the most current advancements in solar power generation devices in order to provide a reference for decision-makers in the field of solar plant construction throughout the world. These technologies are divided into three groups: photovoltaic, thermal, and hybrid (thermal/photovoltaic). As a result, this article begins by outlining the approach that will be employed to undertake this research. Following that, solar energy production methods are researched, and their sub-classifications are described to establish their resource needs and features. Following that, a detailed conversation is held. Each technology's environmental and economic performance will be evaluated. Furthermore, a statistical analysis is conducted to emphasize the efficiency and performance of each solar technology, as well as to identify their global rankings in terms of power output. Finally, research trends in the development of solar power plants are presented. The credibility of the PV system, types, and limitations is the discussion understudy system makes use of the sun's energy to generate electricity with the help of varied procedural systems; stand-alone, hybrid, or grid charged. Based on this research, it is possible to infer that the primary goals of optimization approaches are to reduce investment, operation and maintenance costs, and emissions in order to improve system dependability. This paper also includes a brief overview of several solar energy optimization problems and issues.